On Some Properties of Several Proof Systems for2-valued Propositional Logic - Petrosyan, G. V. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
In this work we investigate the relations between the proofs complexities of minimal tautologies and of results of substitutions in them in some systems of 2-valued classical propositional logic. We show that the result of substitution can be proved easier, than corresponding minimal tautology, therefore the systems, which are considered in this paper, are no monotonous neither by lines nor by size. Հետազոտված է մինիմալ նույնաբանությունների և նրանցում տեղադրությունների արտածման բարդությունների միջև հարաբերությունը որոշակի երկարժեք ասույթային դասական տրամաբանության համակարգերում։ Ցույց է տրվել, որ տեղադրման արդյունք հանդիսացող բանաձևերը կարող են արտածվել ավելի հեշտ, այդ իսկ պատճառով դիտարկված համակարգերը մոնոտոն չեն: Исследована связь между сложностями доказательств минимальных тавтологий и результатами подстановок в них в некоторых системах 2-значной классической логики высказываний. Показано, что результат подстановки доказывается проще, чем соответствующая минимальная тавтология, поэтому рассматриваемые в статье системы не являются монотонными ни по линиям, ни по размеру.
Keywords: Mathematics